Policies that Address Sustainable Site Development - Marisa Romero; Mark E. Hostetler (EDIS, 2007)
Circular 1520, a 9-page document by Marisa Romero and Mark E. Hostetler, compiles and summarizes five city and county ordinances that promote sustainable development at the site development level. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, May 2007.